The Dynamics of Proportionality: Constitutional Courts and the Review of COVID-19 Regulations. - Ladislav Vyhnánek; Anna Blechová; Michael Bátrla; Jakub Míšek; Tereza Novotná; Amnon Reichman; Jakub Harašta (German Law Journal, 2024)
The COVID-19 pandemic has made it clear that even when using trusted legal tools, courts may run into challenging problems. Governments reacted to an unprecedented (at least in the context of post-WW2 era of fundamental rights) global crisis by adopting measures that drastically limited fundamental rights in order to protect the lives and health of many. Courts, of course, were entrusted with protecting fundamental rights against governmental overreach. The question was, how strict should the courts be when reviewing governmental acts. On the one hand, they could have relied on substantive proportionality assessment. This option, however was virtually ignored and most courts have opted for a deferential approach. This article analyzes both of these approaches, their strengths and weaknesses, but ultimately it argues that a third option - semiprocedural review - is the best way out of this judicial conundrum. Relying on comparative as well as theoretical arguments, it argues that semiprocedural review is the best way to deal with challenging empirical question - even under conditions of epistemological uncertainty.